Restoration of length of the femur in patients with consequences of epiphyseal osteomyelitis by means of intramedullary distraction according to Bliskunov - Kutsenko, Sergey; Shpuntov, Olexey; Kutsenko, Yuliya (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Epiphyseal osteomyelitis leads to such severe orthopaedic pathology as destructive hip dislocation, deformity, shortening, contracture, and osteoarthritis. Traditional method of eliminating unequal limb length is extrafocal ostheosyntesis. Objective: to evaluate outcomes in patients with hip shortening after epiphyseal osteomyelitis using intramedullary distraction. Methods: surgeries were performed in 26 patients, shortening of the femur was (7,0 ± 0,5) cm. Surgical technology of implantation of distraction apparatus’ consisted of several phases: mounting of the conductor device, reboring of the medullary canal for the distractor, subtrochanteric osteotomy, implantation of the distraction device and its blocking, implantation of the telescopic actuator and the pelvic node to the wing of ilium. Distraction velocity was (1,0 ± 0,2) mm per day. Results: close-in outcomes were examined in 26 patients, and long-term outcomes in 23 ones. Good results obtained in 22 (95.7 %) patients, and satisfactory results in 1 (4.3 %) one. Any infectious complications were not observed. The devices implanted make it possible to apply methods of rehabilitation treatment on early stages during distraction and fixation. Conclusion: intramedullary distraction is an effective method for surgical correction of anatomic shortening of the hip after epiphyseal osteomyelitis.